Revalidation of the termitophilous genus Ceratoxenus Mann and description of two new species from the Neotropical region (Coleoptera: Staphylinidae: Aleocharinae: Corotocini) - Moreno, Carlos; Zilberman, Bruno (Zootaxa, 2024)
Termitogastrina is a subtribe of termitophilous rove beetles distributed mostly across Neotropical and Afrotropical regions. In 1923, William M. Mann established the genera Ceratoxenus and Xenopelta from material collected by Alfred E. Emerson in Guyana. Nine years later, Emerson himself synonymized the genera, in what seems to be a result from the misidentification of specimens. In this work, we revalidate the genus Ceratoxenus, provide its redescription and a taxonomical key for the species, along with a comparative diagnosis with the genus Xenopelta. Additionally, two new species of Ceratoxenus are described: C. akerata sp. nov. and C. inflatus sp. nov., respectively, from Panama and Guyana. This paper also marks a new record for the genus Ceratoxenus for Panama.